Reconstructing the Performance Management System of a Legal Entity University (PTN-BH) using the SMART Model: a Strategic Approach to Achieving World-Class University - Murdiono, Achmad; Pujianto, Utomo; Raharjo, Swasono; Martha, Jefry Aulia; Murad, Safwan Marwin Abdul (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2024)
The change in status of a Higher Education Institution (PT) to a PTN BH is road going to independence in exploit Resources owned in a way creative and innovative in build Human Resources in Indonesia. In addition, PTNBH is also required own good reputation in ranking national or international. In order to reach objective mentioned, required management institutional apply system management guaranteed performance development sustainable. In addition, the system management developed performance No Again absorption oriented budget, but also optimization budget (efficiency and efficiency). Reconstruction system management performance in study This use SMART approach (Specific, Measurable, Achievable, Relevant, and Time- bound). The approach used in this research This is Research and Development (RnD). Stages study This is (1) stage Study introduction (data collection); (2) stage preparation of grand design; (3) trial stage expert and scale limited; (4) trial and refinement stage scale big. Data is already obtained from results trials will done analysis descriptive For get material as analysis research. Based on model test results obtained results that based on three aspect that is appearance, materials and benefits assessed very well by the work unit leader and capable make it easier time planning in compile plan activities and budget year walk.